Clinical efficacy of integrated traditional Chinese and western medicine in the treatment of oligoasthenospermia in male infertility of kidney-yang deficiency type - Chuchu Gao; Xinxin Hu; Ting Li; Huijun Zheng; Xi Zhou; Peng Li (Journal of Men's Health, 2023)
This study examines the clinically comprehensive effects of Wuzi Shenqi Decoction, an acupoint application that combines traditional Chinese medicine with western medicine on male infertility with oligoasthenospermia of kidney-yang deficiency type. A total of 184 male infertiles with oligoasthenospermia who came to our hospital from April 2022 to June 2023 were randomly assigned to a study group (n = 92) and an experimental group (n = 92). The experimental group was treated with L-carnitine oral solution, while the study group was treated with Wuzi Shenqi Decoction combined with acupoint application based on the experimental group. Before and after treatment, clinical efficacy, semen parameters (semen volume, sperm density, sperm survival rate, sperm motility), sexual hormone parameters (follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone (T), prolactin (PRL), estradiol), and TCM (Traditional Chinese Medicine) syndrome scores were observed and compared between both groups. Before treatment, there was no significant difference in semen parameter index, sexual hormone index and TCM syndrome score between both groups (p > 0.05); after treatment, the semen parameter index and sexual hormone index in both groups were higher than before treatment, and the TCM syndrome score was diminished with a significant difference (p < 0.05). The overall response rate of the study group was 92.39%, which was significantly higher than that of the experimental group (72.83%) (p < 0.05). For male infertility patients with oligoasthenospermia of kidney-yang deficiency type, the use of Wuzi Shenqi Decoction combined with traditional Chinese medicine acupoint application plus L-carnitine oral solution can effectively improve the clinical symptoms of patients, improve semen quality, regulate sex hormone levels, which is worthy of clinical application.